Influence of various environmental factors on the growth of children and adolescents in Jeddah, Kingdom of Saudi Arabia - Al-Agha, Abdulmoein Eid; Adam, Alyaa; Almaghrabi, Anhar; Zainalabidin, Asmaa; Ahmed, Hajar Mohammed; Almuwallad, Rawan A.; Aljahdali, Shaima H.; Alharbi, Shuruq; Alhowig, Wijdan (Acta Biomedica Atenei Parmensis, 2020)
Objectives: To evaluate the association between various environmental factors and the anthropometric measurements of children and adolescents. Methods: This retrospective studywasperformed from September 2017 to April 2018 and included 393 children aged 2-18 years. Data were extracted through patient and/or parentinterviews and from medical records of endocrine ambulatory clinics. Results: Among underweight children,the proportion of mixed-fed children was the highest, and among normal weight children, most were either bottle-fed or mixed-fed. Most overweight children were mixed-fed, and most obese children were breastfed. Underweight status was noted most commonly in children playing videogames for 4 and 2-4 hours/day. Normal weight was noted most commonly in those playing for >4 hours/day, followed by those playing 4 hours/day, followed by those playing 2-4 and